Interspecies Comparison of the Bacterial Response to Allicin Reveals Species‐Specific Defense Strategies. Issue 24 (12th November 2019) - Wüllner, Dominik; Haupt, Annika; Prochnow, Pascal; Leontiev, Roman; Slusarenko, Alan J.; Bandow, Julia E.
Abstract: Allicin, a broad‐spectrum antimicrobial agent from garlic, disrupts thiol and redox homeostasis, proteostasis, and cell membrane integrity. Since medicine demands antimicrobials with so far unexploited mechanisms, allicin is a promising lead structure. While progress is being made in unraveling its mode of action, little is known on bacterial adaptation strategies. Some isolates of Pseudomonas aeruginosa and Escherichia coli withstand exposure to high allicin concentrations due to as yet unknown mechanisms. To elucidate resistance and sensitivity‐conferring cellular processes, the acute proteomic responses of a resistant P. aeruginosa strain and the sensitive species Bacillus subtilis are compared to the published proteomic response of E. coli to allicin treatment. The cellular defense strategies share functional features: proteins involved in translation and maintenance of protein quality, redox homeostasis, and cell envelope modification are upregulated. In both Gram‐negative species, protein synthesis of the majority of proteins is downregulated while the Gram‐positive B. subtilis responded by upregulation of multiple regulons. A comparison of the B. subtilis proteomic response to a library of responses to antibiotic treatment reveals 30 proteins specifically upregulated by allicin. Upregulated oxidative stress proteins are shared with nitrofurantoin and diamide. Microscopy‐based assays further indicate that in B. subtilis cell wall integrity is impaired.